DESCRIPTIVE STUDY OF VOCABULARY MASTERY IN SD IT AL KAUTSAR SECANGGANG - YUSRAH; NENENG SRI LESTARI; Syafii (The Seall Journal, 2022)
This paper investigates the translation shifts on Andrea Hirata’s Laskar Pelangi Into The Rainbow Troops By Angie Kilbane as the consequence of interference of mother language in translating SL into TL. It focuses on the shifts occur in Source Text and Target Text in term of Catford’s category shifts. The Descriptive Translation Studies (DTS) is used in analyzing the texts. The texts are separated in clauses and analyzed based on Catford’s category shifts. It is argued that the interference of First Language affect in translating ST into TT. It was found that: a) unit shift, class shift and the very common one- the structural shift occured i translating the text, b) expanding text occurs in which the TT has explained the more detail than the ST, c) It was also found that there are two kinds of interference between ST and TT i.e. Syntactic/Grammatical interference and Lexical/Semantic interference as shifts are the reflection of the translator’s first language interference)